PENEGAKAN HUKUM ADMINISTRASI NEGARA TERHADAP IZIN PENGELOLAAN HUTAN MENURUT UNDANG-UNDANG NO. 41 TAHUN 1999 TENTANG KEHUTANAN - Alitsha Jasmine Adellea (Indonesian State Law Review, 2021)
Forests are very important in the life and environmental conservation that management needs to be improved in order to realize the role and function optimally. The method used is normative research method is a procedure of scientific research to find out the truth based on scientific logic of the normative legal. As for the forest management permit consists of; forest utilization license, permit utilization of environmental services, permits for harvesting timber and non- timber, each of the production forests and protected areas and permit utilization of timber and non-timber forest production.